Electrokinetic in situ leaching of U from low-permeability uranium ore - Chunguang Li; Wenji Wang; Zhenzhong Liu; Yongmei Li; Qi Liu; Longcheng Liu (Nuclear Engineering and Technology)
In this study, the impacts of electrokinetic in situ leaching of uranium (EK-ISLU) on the pore structure and connectivity of the low-permeability uranium ore and its leaching efficiency were investigated. Our results demonstrated that a direct current field with an intensity of 7.5 V/cm increased the porosity by 7.07 % and enhanced the uranium leaching efficiency by 73.73 % using a sulfuric acid solution. Under electrical stimulation, the leaching agent exhibited uniform penetration ability through combined electromigration and electroosmosis effects, significantly improving the directed migration of the target ions. Various characterization techniques, such as Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy-energy dispersive X-ray spectrometry (SEM-EDS), three-dimensional computed tomography (CT) pore scanning and Brunauer-Emmett-Teller (BET), showed that the electrokinetic-induced action overcame the preferential flow phenomena, promoted the dissolution of the target minerals and gangue rocks, and notably improved the pore structure to ultimately enhance the uranium leaching efficiency. Our results provide valuable insights for the development of innovative technologies aimed at efficiently recovering U from low-permeability uranium ores.